Epidemiology, antimicrobial resistance, and mortality risk factors of carbapenem resistant gram-negative bacteria in hematopoietic stem cell transplantation recipients - Jia, Yan; Li, Yun; Liu, Yi; Yang, Ziyue; Chen, Xuefeng; Liu, Yanfeng (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Carbapenem resistant gram-negative bacteria (CRGNB) infection is more and more frequent in patients after hematopoietic stem cell transplantation (HSCT), and the prognosis is very poor. The purpose of this study was to investigate the clinical characteristics and risk factors for mortality with CRGNB infection in HSCT recipients, and to provide useful information for guiding the application of antibiotics and improving the prognosis in the future. Methods Electronic medical records of CRGNB infected patients who underwent HSCT in Xiangya Hospital from January 1, 2015 to June 30, 2022 were collected. At the same time, 1:1 case-control matching was performed according to gender, age and disease type. The epidemiological characteristics and drug resistance of patients with CRGNB infection and non-CRGNB infection were compared. Logistic regression and Cox regression analysis were used to determine the risk factors for CRGNB acquisition and death respectively, and a prediction model of overall survival was constructed by R language. Results and Discussion The crude infection rate of CRGNB in HSCT recipients was 7.42%, and the mortality rate was 47.1%. CRGNB was resistant to most commonly used antibiotics. Time interval from diagnosis to transplantation >180 days (HR=7.886, 95% CI 2.624-23.703, P=0.000), septic shock (HR=6.182, 95% CI 2.605-14.671, P=0.000), platelet count < 20 × 109/L (HR=2.615, 95% CI 1.152-5.934, P=0.022) and total bilirubin > 34.2 μmol/L (HR=7.348, 95% CI 2.966-18.202, P=0.000) at the initial stage of infection were 4 independent risk factors associated with mortality. CRGNB infection has become a serious threat to HSCT recipients. Clinicians should pay high attention to it and actively seek personalized treatment strategies suitable for local medical conditions.